Implementation of Web-based Student Report Card Score Information Systems in Junior High Schools in Indonesia - Muhammad, Fakhry; Sutomo, Rudi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Education-related businesses are conducted by SMPN 286 West Jakarta. The traditional method of recording and processing student grade data by the concerned teacher frequently results in errors. Hence SMPN 286 intends to develop an integrated system for processing and recording student report cards. Report cards for students are delayed as a result, and processing and recording problems occur when grades are calculated. Record card It also takes a long time to process and record data values manually. The Rapid Application Development (RAD) method will be used to create a report card value information system based on a website. Compared to other ways, work done utilizing the Rapid Application Development (RAD) method is quick and effective; therefore, employing it to construct a report card information system website can be helpful. The SMPN 286 West Jakarta has issues that can be helped and resolved by establishing a website-based report card grade information system. Online information system based on report cards' grades. The concerned instructor does not need to manually process and record value data for students to reduce recording errors, process student report cards, and cut processing times for processing and recording value data.